Do sujeito ao sistema: uma análise do direito na Teoria dos Sistemas de Niklas Luhmann - Machado, Mateus Renard (2012)
The present study has the objective to present some key elements of systems theory of Niklas Luhmann. Systems theory has widely circulated in the past half century, with contributions from biology, cybernetics and mathematics. Luhmann rejects the old tradition based on ontological concepts, the notion of system as a whole composed of parts, the search for the essence of the elements. In exchange initially proposes a systems theory that is guided by the distinction between system and environment. In its mature phase designs functionally differentiated social systems, autopoietic, self-reference and endowed with meaning. The first chapter will be devoted to the presentation of the evolution of systems theory, elements that are common to any social system and to question the place of the subject in theory luhmannian. The second chapter is devoted to communication, synthesis of information, the act of communicating and the act of understanding. Communication is the basic operation of social systems. We'll see how the contact with the psychic and living systems. The third chapter is devoted to the law. This subsystem has the social function of generating expectations of conduct. The self-reference, autopoiesis and select the legal operations of non-legal. The binary code legal / illegal conduct legal communication and indicates the pipes that are nonconforming or conforming to the law. The recursion of operations and the memory of the right, through positive and repeated decisions, reinforce this subsystem normative. Luhmann's work is vast, having numerous references to the tradition of philosophy and sociology, as it appropriates elements of the exact sciences and natural sciences. You can find two phases this author reference in their works. The division occurs in March with the introduction of the concept of autopoiesis, rescued the theory of Maturana and selfreference design and functionality. For all that, the theory developed by Luhmann shows extremely interesting and complex. Keywords: Theory of systems. Self-reference.